Tinjauan Normatif Pembela Hak Asasi Manusia dalam Hukum Internasional dan Hukum Nasional - Ryan Abraham Silalahi (Soegijapranata Catholic University, 2021)
Human rights are acknowledgment that every human being has basic freedom and dignity. With this recognition, everyone has the right to defend and fight for their rights for their existence as a human being. Human Rights Defenders (HRDs) are everyone who works to defend and fight for people's human rights. In international law the rights of Human Rights Defenders are specifically manifested in the 1998 UN Declaration of Human Rights Defenders. Human rights and the extent to which Indonesia provides regulations for these human rights defenders. This study aims to analyze the protection of human rights defenders in the perspective of international law and the application of international law in national legal regulations related to the protection of human rights defenders. This research will use a qualitative normative juridical approach, with analytical descriptive research specifications and data collection techniques through literature study.